2006
DOI: 10.3748/wjg.v12.i22.3609
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-selectin, integrin β1and immunoglobulin superfamily member in human gastric carcinoma cells and its clinicopathologic significance

Abstract: Serum E-selectin, ICAM-1 and integrin beta1 expression levels are probably related to the metastasis and relapse of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Yashiro et al (60) suggested that ICAM-1 facilitates GC cell adhesion to immune cells, leading to immune tolerance (Table II). However, other studies have demonstrated an association between the serum levels of circulating ICAM-1 and GC tumor progression, with higher levels indicating a worse prognosis (53,61,62). On account of the contradictory results in these studies, ICAM-1 has not yet been established as a prognostic marker in GC.…”
Section: Lymphangiogenesis and Metastasismentioning
confidence: 93%
See 1 more Smart Citation
“…Yashiro et al (60) suggested that ICAM-1 facilitates GC cell adhesion to immune cells, leading to immune tolerance (Table II). However, other studies have demonstrated an association between the serum levels of circulating ICAM-1 and GC tumor progression, with higher levels indicating a worse prognosis (53,61,62). On account of the contradictory results in these studies, ICAM-1 has not yet been established as a prognostic marker in GC.…”
Section: Lymphangiogenesis and Metastasismentioning
confidence: 93%
“…Integrins, the principal adhesion receptors of the ECM, are vital for multicellular organisms (52). A strong association has been identified between serum integrin β1 content and tumor staging, LN metastasis and distant metastasis (53). E-cadherin (E-cad) mediates calcium-dependent cell-cell adhesion (54).…”
Section: Lymphangiogenesis and Metastasismentioning
confidence: 99%
“…Blockade of IL-8 binding to its receptor causes a decrease in tumor size, angiogenesis, tumor growth, and metastasis while promoting cancer cell apoptosis (36). ICAM-1 is highly expressed in multiple human cancers as well (37)(38)(39). Although it has not been associated with effects on cancer cell survival, ICAM-1 has been linked to both tumor progression and metastasis through its ability to mediate cell adhesion and extravagation (33,40,41).…”
mentioning
confidence: 99%
“…ICAM-1 expression is known to increase in human gastric carcinoma cells as well, being a predictive factor for patients with gastric carcinoma. 56 Since non-neoplastic cells of the GI tract do not express ICAM-1, it presents an attractive target for therapeutic interventions. 57 The role of ICAM-1 in colonic neoplasms is still under research.…”
Section: Cellular Adhesion Moleculesmentioning
confidence: 99%